(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with social rehabilitation of Old Slavonic heritage in the Ukrainian language at the end of XIX century and beginning of XX century. The author gives the analysis of phonetic, structural and semantic, functional and stylistic peculiarities of Church books vocabulary in publicistic works of Mykhailo Grushevskyi.